Minat Utama Kebijakan Pembiayaan dan Manajemen Asuransi Kesehatan Program Studi Ilmu Kesehatan Masyarakat Jurusan Ilmu Kesehatan - , EKO RAHARJO; , Dr. drg. Julita Hendrartini, M.Kes, AAK. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The Program of Health Insurance Scheme (Jamkesda) in Sleman District developed to pay a premium in addition to the poor that is funded from the district budget (APBD). Cost sharing for health service (in health facilities) by participant of Jamkesda Mandiri nearly 80% and participants with premiums paid from the district budget cost sharing approximately 30%. Some participants complained of cost sharing. Therefore it is necessary evaluation of cost sharing Jamkesda program in Sleman District. Objective: This study aims to identify the determinants of cost sharing by participants of Jamkesda Sleman District undertakes a review of the claim documents, describe the average amount per participant cost sharing and participants' perceptions of the cost sharing. Method: The research was conducted with a case study involving the design of a data source primary and secondary data. Primary data obtained through interviews with selected respondents purposive sampling. Secondary data from claims of Jamkesda Program in Sleman District elected systematic sampling among the independent variables with the dependent variable. The independent variables in this study include suitability of the service with the benefits package, prescribing with formulary and status of hospital. Cost sharing is a dependent variable. Results: The health services that Jamkesda participants received are not according to the benefit package (5.59%), not in accordance with the prescribing formulary of Jamkesda (36.50%), cost sharing participants (38.80%). Incidence of cost sharing has a significant relations with the suitability of prescribing with formulary and the status of hospital. Participants' perceptions of the cost sharing Jamkesda Sleman is variety, but can receive cost sharing policy that is not burdensome (less than 40%). Conclusion: There is a significant correlation between suitability of services with benefits, suitability of prescribing the formulary, and the status of the hospital with cost sharing. Participants' perceptions of the varied cost sharing Jamkesda Sleman. Some of the participants objected, but can receive cost sharing policy. Executable cost sharing participant is less than 40%.